Association of Anesthesiologist Handovers With Short-term Outcomes for Patients Undergoing Cardiac Surgery. (December 2020) - Hannan, Edward L.; Samadashvili, Zaza; Sundt, Thoralf M.; Girardi, Leonard; Chikwe, Joanna; Wechsler, Andrew; Adams, David H.; Smith, Craig R.; Gold, Jeffrey P.; Lahey, Stephen J.; Jordan, Desmond
Abstract : BACKGROUND: Complete handover of anesthesia care to a second anesthesiologist has been demonstrated to be associated with worse short-term adverse outcomes among cardiac surgery patients, but little information from multi-institutional studies is available. METHODS: New York's cardiac surgery registry was used to identify patients who underwent cardiac surgery in New York between 2010 and 2016 with and without complete handovers of anesthesia care. A retrospective observational study with inverse probability treatment weighting (IPTW) based on the propensity score was used to adjust for differences in preoperative patient characteristics while comparing differences in the primary outcome (in-hospital/30 day mortality), major complications in the index admission or within 30 days of the index surgery, readmissions within 30 days, and length of stay. RESULTS: A total of 8.5% of the 103, 102 cardiac surgery procedures involved complete handovers. After adjustment, there was a difference between patients with and without handovers in the primary outcome (2.86% vs 2.48%, adjusted risk ratio [ARR] = 1.15 [1.01–1.31]). There was no difference in readmissions within 30 days (13.7% vs 14.4%, ARR = 0.95 [0.90–1.00]), and the differences in complications and length of stay were not clinically meaningful (adjusted differences of <10%). CONCLUSIONS: Cardiac surgery patients in New York who had complete anesthesia handovers experienced higher short-term mortality rates, but there were no meaningful differences in other outcomes. Unnecessary handovers should be carefully monitored.